Effect of Positive Psychotherapy Based on Virtual Social Networks on Anxiety and Depression Reduction in Veterans with Spinal Cord Injury - M. Firoozy; M. Ramezani Piyani (Afarand Scholarly Publishing Institute, 2018)
Aims: Spinal cord injured veterans' problems significantly affect on psychological health of these people. Because of veterans' disability to move and, consequently, excessive difficulty for going to health centers and attending therapeutic sessions, makes it necessary to carry out remote psychological interventions. Therefore, the purpose of this study was to investigate the effectiveness of positive psychology on decreasing psychological distress among veterans through virtual social networks. Materials & Methods: The present applied research is a semi-experimental study with pre-test and post-test design with control group that carried out among 38 veterans with spinal cord injury in Khuzestan province. They were randomly selected from the list of Martyr and Sacrifices' Foundation of Khuzestan province in 2017 and they were randomly assigned into experimental and control groups (19 people in each group). For data collection, Beck Depression Inventory (BDI-II) and Beck Anxiety Inventory were used in pre-test and post-test. The experimental group received 14 sessions of positive psychotherapy and the control group did not receive any interventions. Data were analyzed by SPSS 22 software using Analysis of Covariance (ANCOVA). Findings: There was a significant difference in post-test scores of depression and anxiety between experimental and control groups and positive psychological intervention significantly reduced depression and anxiety in the experimental group (p=0.001). Conclusion: Positive psychological interventions based on virtual social networks (telegrams)  is effective on anxiety and depression reduction in veterans with spinal cord injury.